Genital herpes as still significant dermatological, gynaecological and venereological problem - Plagens-Rotman, Katarzyna; Przybylska, Renata; Gerke, Katarzyna; Adamski, Zygmunt; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Genital herpes is one of the most commonly diagnosed sexually transmitted diseases and the most common factor in the formation of ulcers and erosions within the mucous membranes. It is characterized by a wide range of clinical symptoms from serous-filled blisters located on the erythematous and oedematous substrate to asymptomatic infection. Due to anatomical differences in the genital tract, there is a more than a 4-fold increase in the risk of a woman being infected by a partner than a man by a woman. In addition, the transmission of herpes simple virus from mother to foetus becomes a serious gynaecological and neonatal problem, especially in women of childbearing age. Despite epidemiological studies, the incidence of genital herpes has not been fully understood, probably due to lack of harmonization of disease reporting systems in many countries, and to difficulties in diagnosis and treatment.